ANALISIS PRESTASI KERJA PERSEMAIAN PADA AREAL KEBUN BIBIT PUTERA PANNJALU UPT CEMPAKA DI KECAMATAN CEMPAKA BANJARBARU KALIMANTAN SELATAN - Nur Vitta Sari; Arfa Agustina Rezekiah; Daniel Itta (Lambung Mangkurat University-Indonesia, 2020)
The achievement of this work is done to identify the necessary work time in the nursery of the Putera Pannjalu seed Garden by knowing the level of efficient work achievement. This research aims to calculate the performance of work on seedlings at the Putera Pannjalu Nursery TIU (Technical Implementing Unit) Cempaka. The working time measurement uses a Cumulative method. Cumulative method is a method used in the actual work time measurement of any working element that the hand continues to run without returning to zero to the end. Work time measurement is performed on each activity cycle. Measuring the performance of seedlings in the plantation of PT. Putera Pannjalu TIU Cempaka consists of filling activities such as polybag, weaning, watering, maintenance and grow grass. Working performance measurement time at 07:30 am to 16:30 pm for seven days. The result of the polybag filling measurement is done by three workers with an average obtained for one week produce 202 polybag/hour/person, for the weaning activities by three workers with an average of 639 polybag/hour/person. While in measuring the performance of watering work performed by two workers get an average work performance of 79,838 polybag/hour/person. On the treatment activities acquired average of 19,739 polybag/hour/person and for the average performance of the work of the material of 14,898 polybag/hr/person. The results of the measurement of work performance in the Putera Pannjalu nursery of TIU Cempaka are influenced by age, sex and duration of work.